Global Market Intelligence Platform Annual Report 2025 - Paguirigan, Neale; Lenaerts, Bert; Bayot, Ruvicyn; Demont, Matty; Ynion, Jhoanne; Badayos, Gerdino; De Leon, Dehner (CGIAR Global Market Intelligence Platform, 2025)
The Global Market Intelligence Platform (GloMIP) is one of the major innovations developed under the Market Intelligence Initiative and advanced through the Breeding for Tomorrow (B4T) Science Program - Market Intelligence (MI) Area of Work. The platform has been used by the CGIAR and partners in the B4T (and previously within the Genetic Innovation Action Area), contributing to the refinement and mapping of value propositions for Target Product Profiles (TPPs) together with the Accelerated Breeding (AB) Area of Work, enhancing interoperability with tools like the CGIAR Breeding Portal, and expanding impact opportunity indicators across CGIAR’s five Impact Areas. Recent improvements have strengthened the features and functionality of GloMIP and its portals, delivering better performance, user experience, and improved modelling of projected benefits indicators for Nutrition and Poverty at national and market segment levels. MI and GloMIP hosts a wide array of market intelligence products, such as briefs, posts, podcasts, while strengthening B4T communications and supporting the launch of the first B4T newsletter. Additionally, the prototyping of the “MI Transfer” portal and MI Briefer mark a strategic step toward supporting the product design standard with synthesized intelligence and evidence-based insights through AI.